Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider the set of inference rules for first order logic (analogous to the ones listed here :

I am stuck in proving the following rule

$$\vdash_{\gamma} \neg \forall x.\phi \implies \exists x. \neg \phi $$

I think it is easy to do this using the notion of soundness and completeness and checking that the left formula is valid when the right is.

However I am not able to prove it using just the formalism of manipulating proof trees with inference rules. Somehow I do not see how to get rid of the negation in $\neg \forall x.\phi$ without applying the rule I want to prove.

Any hints?

share|cite|improve this question
up vote 3 down vote accepted

Would the following work?

1 $\vdash \neg \forall x. \phi$ | Hypothesis

2 $\vdash \neg \phi \implies \exists x. \neg \phi$ by existential generalization

3 $\vdash \neg \exists x. \neg \phi \implies \phi$ by 1,Contraposition

4 $\neg \exists x. \neg \phi \vdash \phi$ by 3

5 $\neg \exists x. \neg \phi \vdash \forall x. \phi$ by 4,Universal Generalization

6 $\vdash \neg \exists x. \neg \phi \implies \forall x. \phi$ by 5,Deduction

7 $\vdash \neg \forall x. \phi \implies \exists x. \neg \phi$ by 6,Contraposition

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.